Awareness of analgesics complications in Saudi Arabia: a cross-sectional study - Amal I. Siddig; Abdulhadi M. Alqahtani; Alia AlShalawi; Marwah Turkistani; Sarah Binbaz; Amal Altowairqi (SpringerOpen, 2020)
Abstract Background All over the world, analgesics are considered one of the most widely used and abused medications. Painkillers such as paracetamol (acetaminophen), non-steroidal anti-inflammatory drugs (NSAIDs), and aspirin currently represent the principal means of pain management. Unfortunately, paracetamol and NSAIDs have dangerous side effects primarily when they are used improperly and without respect to safety rules. This study aims to assess the awareness of the indications, complications, and contraindications of commonly used analgesics. Results A total of 1554 participants responded to the survey, and the findings indicated that the main analgesic used is paracetamol. A proportion of 68.1% of the total number of respondents received their information about analgesic medications from a physician or pharmacist; 95.7% used analgesics when needed, and 70.9% mentioned that they would consult a physician or pharmacist if the pain was not relieved after the use of over-the-counter medications. Nearly 29% were not aware of the possibility of adverse effects of analgesic use. Conclusion The most commonly used analgesic is paracetamol, and most of the participants had a poor level of awareness regarding the complications and side effects of analgesics in general. Our recommendation is to conduct a continuous health education campaign about the use of analgesics.